Factors affecting people's participation in the democratization and development programs of NGOs The case of Pagtinabang Foundation in Ormoc City, Leyte. - Usa, Rafael Jr A. (Tacloban City Rafael A. Usa, Jr., 2009)
Non-Government Organizations are seen today as an active vehicle in the promotion of community development and the delivery of basic social services to rural communities which do not have access to any services from the government. They operate to serve various needs of low-income sectors or the poor communities whether for people/community empowerment, advocacy, livelihood/income generation, public education and provision of social services. The main objective of this study is to identify the different factors (in the individual level, community, government, and society) affecting people's participation in the democratization and development programs of Pagtinabangay Foundation, Inc., a NGO operating in Ormoc City, Leyte. I personally conducted fieldwork research in the different rural communities in Ormoc City to evaluate and observe the state of people's participation on the NGO programs in the locality. I also engaged myself in interviews with some of the farmer beneficiaries of the programs of PFI as well as the officers/staff of the foundation.
This study examines and analyzes the interaction of NGOs and the local people towards democratization and development and how external factors, i.e. military presence, lack of government support for the NGO programs, among others, significantly affect people's participation within the community.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science